BESOEKISCH PROEFSTATION FOR EUROPEAN INVESTORS IN THE DISTRICT OOSTHOEK DUTCH EAST INDIES - Izzah, Latifatul (History Department, Faculty of Humanities, University of Jember, 2023)
In 1870 the Dutch Colonial Government had a new policy towards the Dutch East Indies as its colony. The promulgation of the Agrarische Wet and Agrarische Besluit by the Dutch Colonial Government, it opened opportunities for investors to invest in the Dutch East Indies. European investors flocked to the Dutch East Indies to invest. The business that was run was a plantation, by growing agro-industrial plants that were selling well in the European region at the time. This research used historical methods to explore the secrets behind the courage of European investors to lease land in the Indies, especially the Oosthoek area. The results of the research proved the success of European investors doing business because of the large role of a research laboratory named Besoekisch Proefstation. From this research, there has been a success in minimizing crop failures which impacted the high profits earned by the investors. Keywords: Besoekisch proefstation; European investor; Oosthoek region